Application of intravoxel incoherent motion (IVIM) magnetic resonance imaging in the evaluation of primitive brain tumours. Issue 1 (February 2018) - Catanese, A; Malacario, F; Cirillo, L; Toni, F; Zenesini, C; Casolino, D; Bacci, A; Agati, R
Intravoxel incoherent motion is a potential non-invasive diagnostic tool in brain tumours, without any clear guidelines for its evaluation yet. In our study, we compare intravoxel incoherent motion with dynamic susceptibility contrast magnetic resonance imaging in the quantification of tumour tissue blood perfusion in 28 patients affected by brain tumours, highlighting the issues encountered during the acquisition set-up and post-processing steps. Intravoxel incoherent motion is a new imaging tool and an alternative technique to dynamic susceptibility contrast-magnetic resonance imaging which is of considerable interest at present. This is partly because it does not require the use of a contrast agent and relies on the intrinsic properties of motion in the capillaries of the spins. Compared to dynamic susceptibility contrast-magnetic resonance imaging, the intravoxel incoherent motion technique is also characterised by better resolution because the gadolinium-based contrast agent bolus used in the standard technique results in a variation by more than 50% of the signal coming from the brain. Finally, intravoxel incoherent motion is more sensitive to the incoherent motion that originates from small capillary vessels, while the dynamic susceptibility contrast signal is also contaminated by the input from larger arteries and veins, which may result in an overestimation of the blood volume. Although there are limitations due to the heterogeneity of the sample considered in our study, intravoxel incoherent motion has been shown to be an accurate noninvasive radiological biomarker, useful to distinguish between low and high grade glial tumours.